Sorting nipple castings from malleable cast iron from the result of measuring their residual magnetization - S. G. Sandomirski (Литьë и металлургия, 2019)
The physical principles of magnetic control of the structure of malleable cast iron compact castings are summarized. It reports on the technical features and mode of operation of the automated instrument used for control. The features of formation of remanent magnetization of unhealed castings of nipples from malleable cast iron with bleached surface layer, features of the influence of changes in the layer thickness on the result of magnetization of the castings are established. A criterion for sorting castings with thickness of the bleached layer was developed based on the result of measuring its residual magnetization a given. Recommendations on its use when adjusting the rejection limit for automated magnetic sorting of castings by structure at the Minsk plant of heating equipment are given.